2022
DOI: 10.3390/cells11040680
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 Expression Defines Distinct Functional Activities in the Phenotypic HSC Compartment of a Murine Inflammatory Stress Model

Abstract: The transcription factor PU.1 is a critical regulator of lineage fate in blood-forming hematopoietic stem cells (HSC). In response to pro-inflammatory signals, such as the cytokine IL-1β, PU.1 expression is increased in HSC and is associated with myeloid lineage expansion. To address potential functional heterogeneities arising in the phenotypic HSC compartment due to changes in PU.1 expression, here, we fractionated phenotypic HSC in mice using the SLAM surface marker code in conjunction with PU.1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…2c–f ). The CD41 + compartment includes megakaryocytic cells and their progenitors, and stem cell-like megakaryocyte committed progenitors 27 , 28 . Deletion of IL-1R1 caused significant decrease of Gr-1 + Mac1 + and CD41 + cells in the BM and spleens of IL-1R1cKO; Jak2 VF/VF mice compared to Jak2 VF/VF mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2c–f ). The CD41 + compartment includes megakaryocytic cells and their progenitors, and stem cell-like megakaryocyte committed progenitors 27 , 28 . Deletion of IL-1R1 caused significant decrease of Gr-1 + Mac1 + and CD41 + cells in the BM and spleens of IL-1R1cKO; Jak2 VF/VF mice compared to Jak2 VF/VF mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We did not observe evidence of increased autoimmune inflammatory activity in BM HSPC based on Sca-1 levels, indicating that we did not transplant pristane-induced disease ( Fig S5H, I ). Of note, these data contrast with our previous study showing reduced repopulating activity of HSC from pIC-treated mice (Pietras et al ., 2014), which were based on the less-stringent SLAM definition that does not exclude EPCR-cells with extensive short-term Mk activity (Haas et al ., 2015; Chavez et al ., 2022). Taken together, these data indicate HSC LT retain long-term multilineage repopulating activity in the setting of chronic autoimmune inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown that the EPCR + /CD34 -SLAM cell fraction enriches for cells that retain longterm stem cell activity even in the presence of inflammation (Rabe et al, 2020). Post-transplant, all recipient mice had equivalent levels of donor chimerism in the PB regardless of the HSC LT showing reduced repopulating activity of HSC from pIC-treated mice (Pietras et al, 2014), which were based on the less-stringent SLAM definition that does not exclude EPCR-cells with extensive short-term Mk activity (Haas et al, 2015;Chavez et al, 2022). Taken together, these data indicate HSC LT retain long-term multilineage repopulating activity in the setting of chronic autoimmune inflammation.…”
Section: Hsc Lt From Autoimmune Mice Are a Transplantable Reservoir F...mentioning
confidence: 99%
“…This is in agreement with previous publications showing that SPI1 levels also highlight the HSC heterogeneity with SPI1-low HSCs exhibiting long-term repopulating activity and SPI1-high HSCs exhibiting myeloid lineage priming. 9 Thus, even though work on the role of SPI1 in HSC heterogeneity exist, this was the first evidence that SPI1 may play a role in HEC heterogeneity.…”
mentioning
confidence: 86%